2016
DOI: 10.1016/j.smrv.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for sleep disturbances in older adults: Evidence from prospective studies

Abstract: Summary No systematic review of epidemiological evidence has examined risk factors for sleep disturbances among older adults. We searched the PUBMED database combining search terms targeting the following domains (1) prospective, (2) sleep, and (3) aging, and identified 21 relevant population-based studies with prospective sleep outcome data. Only two studies utilized objective measures of sleep disturbance, while six used the Pittsburgh Sleep Quality Index (PSQI) and thirteen used insomnia symptoms or other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
183
7
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(220 citation statements)
references
References 41 publications
28
183
7
2
Order By: Relevance
“…In Canada [9], a study conducted among cancer patients during the perioperative phase, in which some women had already been submitted to surgery, showed that 36.0% of those with breast cancer had insomnia syndrome (assessed using an adaptation of the Insomnia Interview Schedule). ALND axillary lymph node dissection, CTX chemotherapy, SLND sentinel lymph node dissection, 5-FU 5-fluorouracil a Defined as a score greater than or equal to 11 in the anxiety subscale of the Hospital Anxiety and Depression Scale; N = 501 due to missing data b Defined as a score greater than or equal to 11 in the depression subscale of the Hospital Anxiety and Depression Scale c Defined as a score greater than 5 in the Pittsburgh Sleep Quality Index d N = 481 due to missing data e Patients who had both mastectomy and breast-conserving surgery are reported as mastectomy and patients who had both ALND and SLNB are reported as ALND f All patients began this treatment during the first year of follow-up and remained under treatment at the 1-year follow-up evaluation Our findings of greater odds of poor sleep quality at baseline among those with anxiety and depression are consistent with the literature showing that anxiety and depression are associated with the presence of sleep disturbances in the general population [23][24][25] and in breast cancer patients [26,27]. In fact, insomnia symptoms are one of the diagnostic criteria for several mood and anxiety disorders [28].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In Canada [9], a study conducted among cancer patients during the perioperative phase, in which some women had already been submitted to surgery, showed that 36.0% of those with breast cancer had insomnia syndrome (assessed using an adaptation of the Insomnia Interview Schedule). ALND axillary lymph node dissection, CTX chemotherapy, SLND sentinel lymph node dissection, 5-FU 5-fluorouracil a Defined as a score greater than or equal to 11 in the anxiety subscale of the Hospital Anxiety and Depression Scale; N = 501 due to missing data b Defined as a score greater than or equal to 11 in the depression subscale of the Hospital Anxiety and Depression Scale c Defined as a score greater than 5 in the Pittsburgh Sleep Quality Index d N = 481 due to missing data e Patients who had both mastectomy and breast-conserving surgery are reported as mastectomy and patients who had both ALND and SLNB are reported as ALND f All patients began this treatment during the first year of follow-up and remained under treatment at the 1-year follow-up evaluation Our findings of greater odds of poor sleep quality at baseline among those with anxiety and depression are consistent with the literature showing that anxiety and depression are associated with the presence of sleep disturbances in the general population [23][24][25] and in breast cancer patients [26,27]. In fact, insomnia symptoms are one of the diagnostic criteria for several mood and anxiety disorders [28].…”
Section: Discussionsupporting
confidence: 86%
“…The median time [percentile 25, percentile 75 (P25, P75)] between diagnosis (date of the first histological confirmation) and the baseline evaluation was 25 days (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Data Collectionmentioning
confidence: 99%
“…It is quite evident that higher income is a factor that reduces the mental and psychological concerns of the elderly. Adams (Adams, 2006), Friedman (Friedman et al, 2007) and Smagula (Smagula, Stone, Fabio, & Cauley, 2016) emphasized the positive effect of income on solving the sleep disorders. Our results indicated that the elderly with lower education had poorer sleep quality, but there was no significant difference between education status of the elderly and their sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders in the elderly can be caused by various reason, such as medical disorders, atypical sleep-wake patterns, reduced amount of sleep or poor sleep quality. it should be noted that so Sleep disorders have resulted in the poor quality of life , including induced or complicate physical and mental sicknesses and increase the risk of mortality (Smagula, Stone, Fabio, & Cauley, 2016);besides Poor sleep quality in old age is caused by environment, chronic disease, pain and sleep disturbance and too contributes cardiac illness, depression, falls and accidents. Recent findings show sleep quality plays a key role in maintaining cognitive function in elderly (Landry, Best, & Ambrose, 2015).…”
Section: Original Articlementioning
confidence: 99%
“…In the elderly, the aging of the SCN can lead to a decrease in neuronal activity, which in turn can cause changes in the circadian regulation and secretion of the sleep hormone melatonin [76]. Furthermore, an older population may have more psychological [87] and physiological [88] risk factors for poor sleep.…”
Section: Sleepmentioning
confidence: 99%